Causal attributions cognitive dissonance of behavior staff of internal affairs bodies in an emergency situation. (Journal of actual problems of jurisprudence, 2016)
In article presents the socio-psyhological approach of determination of behavior staff of internal affairs bodies in an emergency situation. Installed constituents of cognitive dissonance, are the distinguishing features of this phenomenon. States that cognitive dissonance is initiated by an internal simultaneous collision of the emotional-psychological state and the rational, site-specific work. Describes the approach of causal attribution state of imbalance of the individual staff member.
Keywords: cognitive dissonance; causal attribution; psychological state; emergency situation